2021
DOI: 10.1186/s13045-021-01149-4
|View full text |Cite
|
Sign up to set email alerts
|

Small extracellular vesicle non-coding RNAs in pancreatic cancer: molecular mechanisms and clinical implications

Abstract: Pancreatic cancer has the worst prognosis among common tumors which is attributed to its aggressive phenotype, diagnosis at advanced, inoperable stages, and resistance to systemic therapy. Non-coding RNAs (ncRNAs) such as microRNAs, long non-coding RNAs, and circular RNAs have been established as important regulators of gene expression and their deregulation has been implicated in multiple diseases and foremost cancer. In the tumor microenvironment, non-coding RNAs can be distributed among cancer cells, stroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 229 publications
(272 reference statements)
0
31
0
Order By: Relevance
“…The most recent study [ 105 ] focusing on the role of ferroptosis in the induction of chemoresistance in gastric cancer assessed the exosomal secretion of miR-522 from CAFs. CAF-induced exosomal miR-522 secretion inhibited ferroptosis in gastric cancer cells by targeting arachidonate lipoxygenase 15 (ALOX15) which in turn blocked lipid-ROS accumulation within the cells.…”
Section: Role Of Exosomes In Resistance To Nab-paclitaxel In Pancreat...mentioning
confidence: 99%
“…The most recent study [ 105 ] focusing on the role of ferroptosis in the induction of chemoresistance in gastric cancer assessed the exosomal secretion of miR-522 from CAFs. CAF-induced exosomal miR-522 secretion inhibited ferroptosis in gastric cancer cells by targeting arachidonate lipoxygenase 15 (ALOX15) which in turn blocked lipid-ROS accumulation within the cells.…”
Section: Role Of Exosomes In Resistance To Nab-paclitaxel In Pancreat...mentioning
confidence: 99%
“…In the tumor microenvironment, non-coding RNAs can be distributed in cancer cells, stromal cells and immune cells through small extracellular vesicles (sEVs) and participate in intercellular communication. Sev-nc RNA can be used as a good diagnostic and prognostic fluid marker for tumors ( Reese and Dhayat, 2021 ; Shin et al, 2021 ; Tang et al, 2021 ). Exosomal-derived long noncoding RNA (lncRNA) TMZ-associated lnc RNA in GBM recurrence (lnc-TALC) modulates the glioblastoma (GBM) microenvironment and reduces the sensitivity of GBM to temozolomide chemotherapy, targeting exosomal-lnc-TALC may overcome TMZ resistance in GBM ( Li et al, 2021b ).…”
Section: Detection Of Exosomesmentioning
confidence: 99%
“…In addition, exosomes play a role in coagulation, antigen presentation, immune regulation, and viral replication. Exosome contents, such as proteins, mRNAs, and miRNAs, have been shown to act in receptor cells, thereby activating multiple signaling pathways ( Kalluri and LeBleu, 2020 ; Wen et al, 2020 ; Rong et al, 2021b ; Wang et al, 2021e ; Reese and Dhayat, 2021 ; Tian et al, 2021 ). Tumor cells can secrete more exosomes than normal cells with some variation in contents, and tumor cell-derived exosomes can provide a suitable microenvironment for tumor development, such as cell proliferation, angiogenesis and metastasis, drug resistance and formation of pre-metastatic microenvironment ( Li and Wang, 2017 ; Yan and Chen, 2020 ).…”
Section: Biological Functions Of Circular Rnasmentioning
confidence: 99%
“…CircRNAs are highly stable and widely expressed in a variety of tissues and body fluids, and thus can be used as potential diagnostic and prognostic biomarkers. Studies have shown that circRNAs are abundant and stable in exosomes, and some circRNAs are more highly expressed in blood than in tissues ( D'Ambrosi et al, 2021 ; Reese and Dhayat, 2021 ; Tian et al, 2021 ; van Zonneveld et al, 2021 ). The high expression and stability of circRNAs in body fluids would be more beneficial for their clinical applications ( Bu et al, 2021 ; Fontemaggi et al, 2021 ; Wang et al, 2021h ; Zhao et al, 2021 ).…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%